The Influence of Leadership and Work Motivation on the Performance of PT Bank SulutGo Employees Sam Ratulangi Sub-Branch - Kures, Pingkan Viola Cia; Pio, Riane Johnly; Asaloei, Sandra Ingried (Productivity, 2024)
Human resource management is a means of improving human quality by improving human resources and increasing the performance and output of the organization so that it can produce employees with good performance. There are several factors that can influence human resources in a company or organization, including leadership and work motivation. The aim of this research is to determine the influence of Leadership on the Performance of Employees of PT Bank SulutGo Sam Ratulangi Sub Branch, determine the influence of Work Motivation on the Performance of Employees of PT Bank SulutGo Sam Ratulangi Sub Branch and to determine the influence of Leadership and Work Motivation on the Performance of PT Bank SulutGo Employees Sam Ratulangi Manado Sub-Branch. The type of research used is quantitative research with correlation analysis techniques, regression data analysis, instrument testing, and classical assumption testing. The sampling technique in this research was saturated sampling with a total sample size of 30 employees of PT Bank SulutGo, Sam Ratulangi Sub-Branch. The results of the research show that Leadership has a significant effect on the performance of employees of PT Bank SulutGo Sam Ratulangi Manado Branch, Work Motivation has a significant effect on the Performance of PT Bank SulutGo Employees of Sam Ratulangi Manado Branch and simultaneously Leadership and Work Motivation have a significant effect on the Performance of Employees of PT Bank SulutGo Sub Branch Sam Ratulangi.